MENINGKATKAN HASIL BELAJAR DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN MEDIA GAMBAR DI KELAS IV SD NEGERI 35 AMBACANG KAMBA KECAMATAN BAYANG - ROSITA YANTI ROSITA YANTI (FKIP UMSB, 2018)
Before performing the first teacher learning teachers need to draft the implementation of learning according to the learning steps. Draft Implementation Learning (RPP) by using the media image contains standards of competence, basic competence, indicators, learning objectives, subject matter, learning activities, methods / sources / media, as well as evaluation. Implementation of social studies learning by using media images in accordance with the steps for using the media image that consists of 9 steps starting with setting up tools and materials to be used for learning, deliver learning objectives, provide an introduction to generate interest of students, demonstrating a picture, ask opinion of the students, explains the material through the medium of pictures, ask questions, concluded the subject matter, and provide an evaluation. IPS implementation of learning by using media carried pictures of two cycles, each cycle consisting of two meetings with four stages: planning, implementation, observation, and reflection. Learning by using media images can improve the learning outcomes of students were seen on average over the second cycle learning outcomes increased from the first cycle, in which the first cycle average gained 6.8. While the second cycle the average obtained is 8.1 Keywords: Media Image, Learning Outcomes, IPS